Facile synthesis of low-cost Co-Cu/C alloy catalysts for hydrogen-rich syngas production from low-temperature steam reforming of biomass tar. (5th March 2023) - Wang, Zhi-Hao; Cao, Jing-Pei; Tang, Wen; He, Zi-Meng; Yang, Fei-Long; Wang, Ze-Ying; Zhao, Xiao-Yan
Graphical abstract: Highlights: Modified lignite can serve as a potential material for metal ions recovery. The facile co-ion exchange method can effectively avoid metal agglomeration. Co-Cu/C shows excellent catalytic activity and stability under low temperature. The addition of Cu contributes to lower Co particle size (4.17 nm). The formation of Co-Cu alloy promotes the resistance to deposited carbon and oxidation. Abstract: Recovering beneficial metal ions from industrial effluents by suitable support can be an efficient and environment-friendly way to prepare specific catalysts directly. Herein, modified lignite was developed as an ion exchange material and used to prepare Co-Cu bimetallic catalysts for hydrogen-rich syngas production from steam reforming reactions. For all the catalysts studied, Co75 Cu15 /600 (carbonization temperature at 600 °C) exhibits the optimal catalytic activity and stability in both steam reforming of toluene and biomass tar under low temperatures. Fresh and spent catalysts were detailedly characterized to investigate the metal interactions and catalyst deactivation. The introduction of Cu contributes to the formation of Co-Cu alloy and the lower particle size of Co (4.17 nm), thereby suppressing the carbon deposition, the oxidation of metals and the change of catalyst structure after reaction. Therefore, the inexpensive and readily-available Co-Cu/C has the potential to serve as a promising catalyst for large-scale biomass gasification technology.